Reflections on the importance of financial support for brazilian scientific research with natural products (Research, Society and Development, 2021)
This work proposed a reflection on the importance of financial support for Brazilian scientific research with natural products. A literature review was carried out with scientific articles, federal laws, websites for research funding agencies and portals with relevant subjects to the theme. The chain of natural products is wide and the application of the food, pharmaceutical and cosmetics industry stands out. Many of the industrial models still bring raw materials and antagonistic processes to the sustainable models, as it is understood that in addition to the products being natural, the entire chain must be sustainable, considering the bases of economic, social and environmental development. This is a reflection of the market change as a result of the awareness of consumers and organizations about sustainability aspects, bringing to light the debate on topics such as the 2030 Agenda, the Sustainable Development Goals (SDGs), the use of natural resources, the bioeconomy, with all subjects based on the need for innovation and development. Thus, there is a demand on the part of the private sector in relation to applied research with natural products and for research laboratories there is also an opportunity to obtain private resources to the detriment of public resources. Therefore, it is essential for researchers in the natural product research line to know the viable options for financial support to continue their lines of research, expand their research groups and seek partnerships with the public and private sector.